THE ARMY OF THE REPUBLIC OF UZBEKISTAN - Teshaboyeva , Nafisa; Muxtorova , Ruxshona (Effective scientific journals, 2025)
The Armed Forces of the Republic of Uzbekistan were established in 1992 following independence, dedicated to safeguarding national sovereignty, territorial integrity, and the peaceful life of the population. They comprise Ground Forces, Air and Air Defence Forces, operating in close coordination with the National Guard, border troops, and special services. In recent years, under President Shavkat Mirziyoyev's leadership, extensive modernization has been implemented, including advanced weaponry, drones (UAVs), artificial intelligence technologies, robotic systems, and automated command structures. In 2025, Uzbekistan ranks 58th out of 145 countries in the Global Firepower index, recognized as one of Central Asia's strongest militaries. The defense budget is approximately 2.8–3 billion, with enhanced international partnerships and joint exercises. The Armed Forces not only fulfill defensive roles but also contribute to regional stability.